Manajemen Pendidikan Islam Berbasis Life Skill pada Pesantren Al-Hidayah Terpadu Provinsi Jambi (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to describe and analyze the implementation of life skills-based Islamic education management at the Al-Hidayah Integrated Islamic Boarding School in Jambi Province. The study used a descriptive qualitative approach, combining observation, in-depth interviews, and documentation studies to obtain a comprehensive overview of the ongoing managerial process. The results indicate that the implementation of life skills-based Islamic education management is carried out through four main management functions: planning, organizing, implementing, and evaluating. Each function is designed to integrate Islamic values ​​with the development of skills relevant to the students' lives. The Islamic boarding school emphasizes strengthening personal, social, academic, and vocational skills, systematically integrated into the curriculum and activities. This approach not only enhances practical skills but also fosters religious character, independence, and prepares students to face the demands of the modern era. These findings confirm that effective and targeted educational management is key to developing a competent and competitive generation of students.